Coronaviruses - viruses marking the 21st century - Jemeršić, Lorena (Array, 2020)
Coronaviruses are causative agents of respiratory, gastrointestinal and neurological infections in mammals and birds. The main characteristic of coronaviruses is a high mutation rate, resulting in possible changes in their pathogenicity, tissue tropism or in their host. Even though they have been known causes of disease for decades, they became interesting in the 21st century due to outbreaks of large epidemics in humans and causing serious economic losses in the animal production sector, primarily the pig industry. The outbreaks of the highest concern emerged in 2002 (Severe Acute Respiratory Syndrome ‒ SARS) and in 2012 (Middle-East Respiratory Syndrome ‒ MERS). Both diseases are of animal origin, and manifested with severe pneumonia in humans and a lethality of 11% and 36%, respectively. Today we are confronted with one of the largest epidemics in the history of humankind, the COVID-19 pandemic. It is caused by a variant of the SARS coronavirus and transmitted through person to person contact, with no known animal vector. Until the time of press of this article the infection has been detected in over 4.8 million people and has been the cause of over 320,000 deaths. In Croatia, due to protective measures imposed by the National Civil Protection Headquarters, COVID-19 is still within linear case growth. This review provides insight into known coronavirus infections in animals and humans and shows that novel coronaviruses have already marked the 21st century and likely changed the world, as we know it, forever.